Perancangan Sistem Informasi Penjualan Berbasis Website pada Coffee Singa - Alvino Octaviano; Sofa Sofiana; Agus Nawan (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
At Coffee Singa, recording and processing data on goods, quantities and prices of goods, as well as sales transaction data is still done using handwriting. The difficulty of recording and estimating the number of types of goods, the number of goods, and also the amount of the price, resulted in the data obtained being inaccurate. To improve the accuracy of the data, it is necessary to develop a computerized sales information system. The Web-based Sales Information System application at Coffee Singa is made using the Php programming language, Adobe XD software as the main interface maker and MySQL as the database. This program allows users to enter data, edit data, delete data, search data, filter data and print data to paper media. The data entered is in the form of data on goods, data on types of goods and sales of goods. While the output produced by this information system is in the form of data reports about goods and sales of goods with a Thermal printer to print sales transactions directly. This sales application can be a solution that can be used to make it easier for sellers to process data on sales of goods, and make reports on goods data, reports on purchases and sales of goods, selling goods becomes easier, faster and more efficient. The method used for system development uses the Waterfall method.